Physical Fitness Profile of Male Students Participating in a Junior High School Futsal Extracurricular Program - Syafi'i Syafi'i (Multidisciplinary Journal of Tourism, Hospitality, Sport and Physical Education, 2024)
Purpose of the study: This study aimed to determine the physical fitness level of male students participating in the futsal extracurricular program at MTs Hasanah Pekanbaru. Methodology: This study employed a descriptive quantitative research design. The population consisted of 25 male students participating in the futsal extracurricular program at MTs Hasanah Pekanbaru, selected using total sampling. Data were collected using the Indonesian Physical Fitness Test for boys aged 13–15 years, including a 50-meter sprint, 60-second pull-up test, 60-second sit-up test, vertical jump test, and 1,000-meter run. Data were analyzed using descriptive statistics and percentage analysis. Main Findings: The results showed that the physical fitness level of the students was predominantly in the moderate category. Of the 25 participants, 15 students (60%) were classified as moderate, 3 students (12%) as good, 5 students (20%) as poor, and 2 students (8%) as very poor, while no student achieved the very good category. The overall average fitness score was 14.56, which falls within the moderate classification according to the Indonesian Physical Fitness Test norms. Novelty/Originality of this study: This study provides an updated profile of physical fitness among junior high school students involved in extracurricular futsal activities using the Indonesian Physical Fitness Test framework. The findings offer practical baseline data for coaches, physical education teachers, and schools to design evidence-based training programs that enhance students’ fitness levels and support better participation and performance in school sports activities.